DEVELOPMENT OF THE COMPOSITION AND MANUFACTURING TECHNOLOGY OF ORAL DISPERSIBLE TABLETS WITH A HERBAL SUBSTANCE FROM AJANIA FRUTICULOSA - JAKIYANOV AMANGELDY MURATOVICH (Research Retrieval and Academic Letters, 2025)
This article presents the results of the pharmaceutical development of oral dispersible tablets containing a herbal substance from Ajania fruticulosa. The studies focused on creating oral dispersible tablets with antibacterial and antifungal activity. The developed composition and manufacturing technology are protected by the utility model patent of the Republic of Kazakhstan No. 10003, “Pharmaceutical composition from a herbal substance with antibacterial and antifungal activity and the method for its production.” A plant-derived substance in the form of a dry extract of Ajania fruticulosa (1.5%, 3.75 mg) is used as the active pharmaceutical ingredient. The following excipients are justified and employed: sorbitol (90.9%, 227.25 mg) and/or isomalt as a filler to improve texture and solubility, copovidone (KoVidone® VA64) (5.0%, 12.5 mg) as a binder to ensure oral dispersible tablets strength, talc (2.0%, 5.0 mg) and magnesium stearate (0.1%, 0.25 mg) as glidants and lubricants, as well as menthol oil (0.5%, 1.25 mg) to enhance organoleptic properties. Direct compression was selected as the optimal tableting technology. Quality criteria for the oral dispersible tablets with Ajania fruticulosa extract have been established in accordance with pharmacopeial requirements, and a quality specification has been developed.